TOWARDS INTEGRATING FORENSIC ACCOUNTING IN UNIVERSITY CURRICULA: EVIDENCE FROM STUDENT PERCEPTIONS - MILOJEVIĆ, Stefan; MATEJIĆ, Tijana; MILOŠEVIĆ, Miloš; RESIMIĆ, Milan (Journal of process management and new technologies, 2025)
The subject of this paper is the perception of students regarding the discipline known as forensic accounting. The aim of the paper is to identify the challenges related to the broader application of this discipline in management and information technology studies. The analysis was conducted on a sample of 70 management and IT students from the University of Belgrade, enabling a preliminary assessment of perception and the potential for improving educational and institutional mechanisms to further affirm forensic accounting in higher education and business practice. The obtained results were interpreted using descriptive statistics, Spearman’s correlation analysis, and exploratory factor analysis, aiming to identify latent dimensions that shape student attitudes toward this interdisciplinary field.
Keywords: Forensic accounting; Curricula; Students perceptions